Simultaneous generation of residue-free reactive oxygen species and bacteria capture for efficient electrochemical water disinfection - Yong Liu; Lihao Wang; Qianhui Ma; Xingtao Xu; Xin Gao; Haiguang Zhu; Ting Feng; Xinyue Dou; Miharu Eguchi; Yusuke Yamauchi; Xun Yuan (Nature Communications)
Abstract Residue-free and highly efficient techniques for drinking water disinfection are urgently needed. Herein, we report an electrochemical water disinfection system equipped with atomically precise Ag28 nanoclusters (NCs) as electrode materials. The deployment of these Ag28 NCs not only provides sufficient electrosorption sites for intelligent microbe enrichment but also ensures high-efficiency dual-mode microbial killing through the in situ electrocatalytic production of residue-free reactive oxygen species (ROS) and the inherent antimicrobial activity of Ag28 NCs. Moreover, the design of the system enables a cyclical “alive microbe capture–killing–dead microbe desorption” process for continuous water disinfection. On this basis, this water disinfection system is efficient against broad-spectrum microbes (with >99.99% antimicrobial activity), durable (with a performance reduction of only 0.75% over 40 cycles and 99.90% antimicrobial efficiency for over 5 h of continuous operation), versatile (i.e., other NCs can be used), scalable (with water productivity of 213.33 L h−1 m− 2), energy efficient (with a low energy consumption of 4.91 Wh m− 3; 1.04 Wh m− 3 without the pumping cost) and applicable for various real water samples. This study may open new avenues for global water disinfection techniques.